SPP1+ TAM: CD8+ T Cell Crosstalk Associates with Blocking Radiotherapy Efficacy in Lung Cancer - Yuzhao Jin; Yuan Zhuang; Peng Luo; Xiaojie Zhang; Jinhua Luo; Yifei Ma; Dandan Guo; Na Hang; Qing Li; Zhijun Shen; Zhao Xie; Ruiqing Gao; et al. (Research)
Radiotherapy (RT) is a cornerstone treatment for non-small cell lung cancer (NSCLC), but its efficacy is often limited by immune suppression in the tumor microenvironment. In this study, we identified SPP1 as a key factor up-regulated after RT, mainly expressed by immunosuppressive macrophages. Single-cell RNA sequencing and in vivo models showed that SPP1+ macrophages inhibit CD8+ T cell infiltration and correlate with poor prognosis. Targeting SPP1 in macrophages enhanced RT efficacy, reduced tumor burden, and restored antitumor immunity. In summary, combining RT with SPP1+ macrophage-targeted intervention may serve as a promising strategy to overcome immune-mediated radioresistance and enhance therapeutic efficacy in NSCLC.